Barriers to "last mile" financial inclusion: cases from northern Kenya. Issue 8 (17th November 2019) - Tiwari, Jaya; Schaub, Emily; Sultana, Naziha
ABSTRACT: Financial products and services empower women to grow businesses, survive shocks, accumulate wealth, and take more control over their finances. The BOMA Project supports ultra-poor women in northern Kenya through business and savings groups and a digital financial product. Participants substantially increased income and savings, leading to increased household decision-making power, and education and nutrition expenditure. However, BOMA also observed that illiteracy, innumeracy, and unfamiliarity with technology were barriers to full uptake of the digital product. BOMA's experience highlights the need for simpler tools designed thoughtfully for the target population, and time for participants to learn to use them.